Peaceful Utilization of Transboundary Reservoir in Continental Shelf of Ambalat - Gede Khrisna Kharismawan; I Gede Pasek Eka Wisanjaya (Udayana Journal of Law and Culture, 2022)
Maritime boundaries between Indonesia and Malaysia in Ambalat have not been settled yet. This block is located on a continental shelf that is rich in transboundary reservoirs of hydrocarbons such as oil and gas. Malaysia as a coastal state wants to apply archipelagic state’s boundary, whereas Indonesia as an archipelagic state has applied for an extension of its continental shelf to the United Nations. Therefore, there is still unsettling business to be done in this area to fully utilize transboundary reservoirs in peace. This article aims to seek for way of solving the recurring conflict and utilizing transboundary reservoir in peaceful manner. This article is formulated using normative legal research based on statute, case, and conceptual approaches. This article concludes that differences between states on setting its boundaries is based on interpretation and is driven by economic value of resources, while there is opportunity to peacefully utilize transboundary reservoir by means of joint development based on international practices.